Roles of Pannexin-1 Channels in Inflammatory Response through the TLRs/NF-Kappa B Signaling Pathway Following Experimental Subarachnoid Hemorrhage in Rats - Wu, Ling-Yun (Front Mol Neurosci, 2017)
Background: Accumulating evidence suggests that neuroinflammation plays a critical role in early brain injury after subarachnoid hemorrhage (SAH). Pannexin-1 channels, as a member of gap junction proteins located on the plasma membrane, releases ATP, ions, second messengers, neurotransmitters, and molecules up to 1 kD into the extracellular space, when activated. Previous studies identified that the opening of Pannexin-1 channels is essential for cellular migration, apoptosis and especially inflammation, but its effects on inflammatory response in SAH model have not been explored yet. Methods: Adult male Sprague-Dawley rats were divided into six groups: sham group (n = 20), SAH group (n = 20), SAH + LV-Scramble-ShRNA group (n = 20), SAH + LV-ShRNA-Panx1 group (n = 20), SAH + LV-NC group (n = 20), and SAH + LV-Panx1-EGFP group (n = 20). The rat SAH model was induced by injection of 0.3 ml fresh arterial, non-heparinized blood into the prechiasmatic cistern in 20 s. In SAH + LV-ShRNA-Panx1 group and SAH + LV-Panx1-EGFP group, lentivirus was administered via intracerebroventricular injection (i.c.v.) at 72 h before the induction of SAH. The Quantitative real-time polymerase chain reaction, electrophoretic mobility shift assay, enzyme-linked immunosorbent assay, immunofluorescence staining, and western blotting were performed to explore the potential interactive mechanism between Pannexin-1 channels and TLR2/TLR4/NF-κB-mediated signaling pathway. Cognitive and memory changes were investigated by the Morris water maze test. Results: Administration with LV-ShRNA-Panx1 markedly decreased the expression levels of TLR2/4/NF-κB pathway-related agents in the brain cortex and significantly ameliorated neurological cognitive and memory deficits in this SAH model. On the contrary, administration of LV-Panx1-EGFP elevated the expressions of TLR2/4/NF-κB pathway-related agents, which correlated with augmented neuronal apoptosis. Conclusion: Pannexin-1 channels may contribute to inflammatory response and neurobehavioral dysfunction through the TLR2/TLR4/NF-κB-mediated pathway signaling after SAH, suggesting a potential role of Pannexin-1 channels could be a potential therapeutic target for the treatment of SAH.